THE INFLUENCE OF VILLAGE POLICIES, COMMUNITY PARTICIPATION, CAPACITY OF BUMDES MANAGEMENT ON VILLAGE ECONOMIC DEVELOPMENT IN SOUTH AMFOANG DISTRICT - Lexi F. Kasse; Frans Gana; M. U. K. Yewang; Arifin Arifin (Postgraduate School, Universitas Nusa Cendana, 2020)
Village-owned enterprises (BUMDes) are village business institutions managed by the community and village government in an effort to strengthen the village economy and are formed based on the needs and potential of the village. In Kupang district, especially South Amfoang sub-district, which consists of 6 villages, there are several BUMDes programs implemented, namely savings and loans, village kiosks and cattle fattening. These villages are still lagging behind in terms of poor infrastructure, inadequate access to information, minimal human resources and population income that is still below average. This of course will affect the development of the village economy. This study aims to determine the description of village policy data. This study aims to determine the description of village policy data, community participation, and the capacity of BUMDes managers in the context of village economic development, to analyze the direct effect of village policies, community participation and the capacity of BUMDes managers on village economic development in South Amfoang sub-district. The method used in this research is quantitative research which is regressive in nature, namely research conducted to find the influence of policies, community participation and the capacity of BUMDes managers on economic development in 6 villages located in Amfoang Selatan sub-district, Kupang district. The results of this study indicate that there is a positive and significant effect. It can be seen from the indicators of village policies, the better the policies are made, the village economy will develop, community participation has a positive and significant effect on economic development. It can be seen from the indicators of community participation, the higher the level of community participation, the efforts to develop the village economy will run as planned, the capacity of BUMDes managers has a positive and significant effect on economic development. Village policies, community participation and the capacity of BUMDes managers collectively have a positive and significant impact on economic development.